Composition for low dielectric heat dissipation film and low dielectric heat dissipation film
By using a maleimide resin composition and a composition of boron nitride particles in the printed wiring board material, the problem of insufficient transfer loss and heat dissipation in the high frequency range is solved, and low dielectric constant and high thermal conductivity are achieved balance effect.
Patent Information
- Application Number
- CN202010268080.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-10
- Filing Date
- 2020-04-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-04-08
AI Technical Summary
It is difficult to develop a printed wiring board material that can reduce transfer losses in a high frequency range and has high heat dissipation.
Using a composition for a low dielectric heat dissipation film, the composition comprises a maleimide resin composition and boron nitride particles, and the orientation of the maleimide resin composition and boron nitride particles is achieved by adjusting the orientation of the maleimide resin composition and boron nitride particles. Relative dielectric constant and high thermal conductivity.
A balance between low dielectric constant and high thermal conductivity in the high frequency range is achieved, and it is suitable for printed wiring board materials for high frequency electronic equipment.
Smart Images

Figure CN111808421B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composition for a low dielectric heat dissipation film and a low dielectric heat dissipation film. Background Art
[0002] In recent years, the high-speed and large-capacity signals used by mobile communication devices represented by mobile phones, network infrastructure equipment such as base station equipment, servers, routers, and electronic devices such as large computers have been developed year by year. Along with this, the printed wiring boards carried by these electronic devices need to cope with high frequencies such as the 20GHz region, and seek a substrate material with a low relative dielectric constant and a low dielectric loss factor that can reduce transmission loss. In addition to the above-mentioned electronic devices, in the field of intelligent transportation systems (ITS) (related to automobiles and transportation systems) and indoor short-range communication fields, the practical application and practical plans of new systems that can handle high-frequency wireless signals are also constantly progressing, and for the printed wiring boards carried by these devices, it is also required to be a low transmission loss substrate material. In addition, due to the large heat generation of these electronic devices and printed wiring boards, the performance also decreases accordingly, so the materials used are also required to have high heat dissipation.
[0003] It is known that commonly used high thermal conductive fillers such as metal oxides and metal nitrides have high relative dielectric constants and are not suitable as materials for high frequencies, while boron nitride has a low relative dielectric constant and a very high thermal conductivity in the a-axis direction. However, since the thermal conductivity in the c-axis direction is low and it is difficult to synthesize spherical boron nitride, high thermal conductivity cannot be obtained when it is made into a resin composition.
[0004] In addition, polyphenylene ether (PPE) resins, maleimide resins, and fluororesins that exhibit excellent high-frequency characteristics are used as printed wiring boards that require low transmission loss. However, these materials have low thermal conductivity and are insufficient as materials for high frequencies (Patent Documents 1 to 4).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2010-59363
[0008] Patent Document 2: Japanese Patent Application Publication No. 2010-275342
[0009] Patent Document 3: Japanese Patent Application Publication No. 2012-255059
[0010] Patent Document 4: Japanese Patent Re-Publication No. 2016-114287 Summary of the invention
[0011] Technical Problems to be Solved by the Invention
[0012] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a film composition which provides a film having a low dielectric constant and high heat dissipation properties.
[0013] Technical means to solve technical problems
[0014] In order to achieve the above object, the present invention provides a composition for low dielectric heat dissipation film, which comprises the following components (A) and (B):
[0015] (A) a maleimide resin composition;
[0016] (B) Boron nitride particles,
[0017] The component (A) contains the following components (A1) and (A2):
[0018] (A1) a maleimide resin having at least two maleimide groups in one molecule;
[0019] (A2) a polymerization initiator,
[0020] The maleimide equivalent of the component (A1) is 0.1 mol / 100 g or less, and the relative dielectric constant of the cured product of the component (A) at a frequency of 10 GHz is 3.5 or less.
[0021] The composition for low dielectric heat dissipation film provides a film having low relative dielectric constant and high thermal conductivity.
[0022] The boron nitride particles of the component (B) preferably include boron nitride particles having a hexagonal crystal structure.
[0023] If the boron nitride particles of the component (B) include hexagonal boron nitride particles, the low dielectric heat dissipation film composition provides a film having high thermal conductivity by utilizing the property that the hexagonal boron nitride particles have high thermal conductivity in the a-axis direction.
[0024] The maleimide resin as the component (A1) preferably has a main chain including an alkylene chain (phenylene chain) or an arylene chain (arylene chain) having 12 or more carbon atoms.
[0025] When the maleimide resin of the component (A1) has a main chain including an alkylene chain or an arylene chain having 12 or more carbon atoms, the relative dielectric constant of the cured product of the component (A) can be suppressed to be low.
[0026] The ratio Ia / Ic of the intensity Ia in the a-axis direction (100 plane) and the intensity Ic in the c-axis direction (002 plane) of the boron nitride particles of the component (B) measured using an X-ray diffractometer is preferably 0.25 or more.
[0027] If the ratio Ia / Ic of the boron nitride particles of the component (B) is 0.25 or more, the composition for a low dielectric heat dissipation film provides a film having a high thermal conductivity in the thickness direction of the film.
[0028] The composition for low dielectric heat dissipation film preferably further contains at least one selected from epoxy resin, phenylene ether resin, styrene resin, and phenol resin as component (C).
[0029] The low dielectric heat dissipation film composition containing the component (C) provides a film having a lower relative dielectric constant and a higher thermal conductivity.
[0030] Furthermore, the present invention provides a low dielectric heat dissipation film, which is a molded product of the composition for low dielectric heat dissipation film.
[0031] The low dielectric heat dissipation film has low relative dielectric constant and high thermal conductivity.
[0032] The difference in thermal conductivity between the surface direction and the thickness direction of the low dielectric heat dissipation film is preferably 0.5 W / m·K or more.
[0033] When the difference in thermal conductivity is 0.5 W / m·K or more, at least a portion of the boron nitride particles are oriented in the thickness direction of the film, and thus the thermal conductivity of the low dielectric heat dissipation film is anisotropic.
[0034] Effects of the Invention
[0035] The present invention can provide a film composition having a low relative dielectric constant and high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of hexagonal boron nitride particles.
[0037] Figure 2 Schematic diagram of a film with oriented boron nitride particles. DETAILED DESCRIPTION
[0038] As described above, there has been a demand for the development of a film composition that provides a film having a low relative dielectric constant and high thermal conductivity.
[0039] The inventors of the present application have repeatedly and seriously studied the above technical problems, and found that the following low dielectric heat dissipation film composition can solve the above technical problems, thereby completing the present invention:
[0040] A composition for a low dielectric heat dissipation film, comprising the following components (A) and (B):
[0041] (A) a maleimide resin composition;
[0042] (B) Boron nitride particles,
[0043] The component (A) contains the following components (A1) and (A2):
[0044] (A1) a maleimide resin having at least two maleimide groups in one molecule;
[0045] (A2) a polymerization initiator,
[0046] The maleimide equivalent of the component (A1) is 0.1 mol / 100 g or less, and the relative dielectric constant of the cured product of the component (A) at a frequency of 10 GHz is 3.5 or less.
[0047] That is, the present invention is a composition for a low dielectric heat dissipation film, which comprises the following components (A) and (B):
[0048] (A) a maleimide resin composition;
[0049] (B) Boron nitride particles,
[0050] The component (A) contains the following components (A1) and (A2):
[0051] (A1) a maleimide resin having at least two maleimide groups in one molecule;
[0052] (A2) a polymerization initiator,
[0053] The maleimide equivalent of the component (A1) is 0.1 mol / 100 g or less, and the relative dielectric constant of the cured product of the component (A) at a frequency of 10 GHz is 3.5 or less.
[0054] Hereinafter, the low dielectric heat dissipation film composition of the present invention will be described in detail.
[0055] [(A) Maleimide resin composition]
[0056] The component (A) of the present invention is the main component of the composition for low dielectric heat dissipation film of the present invention, and contains the following two components: (A1) a maleimide resin containing at least two maleimide groups in one molecule; and (A2) a polymerization initiator.
[0057] (A1) A maleimide resin containing at least two maleimide groups in one molecule
[0058] The component (A1) of the present invention contains at least 2 or more, preferably 2 to 4 maleimide groups in one molecule, and the maleimide equivalent is 0.1 mol / 100 g or less, preferably 0.08 mol / 100 g or less, and more preferably 0.001 to 0.06 mol / 100 g. If the maleimide equivalent is greater than 0.1 mol / 100 g, the relative dielectric constant of the cured product of the component (A) cannot be suppressed to a low level, which is not preferred. The maleimide equivalent is determined, for example, by measuring the 400 MHz 1 The H-NMR spectrum was calculated based on the integrated value of hydrogen atoms obtained using dimethyl sulfoxide as an internal standard.
[0059] The component (A1) preferably has a main chain including an alkylene chain or an arylene chain having 12 or more carbon atoms, and more preferably has a main chain including an alkylene chain or an arylene chain having 14 to 50 carbon atoms. If the number of carbon atoms is within this range, the relative dielectric constant of the cured product of the component (A) can be suppressed to a low level, which is preferred.
[0060] As maleimide of (A1) component, the maleimide compound represented by following (1) is mentioned, for example.
[0061] [Chemical formula 1]
[0062]
[0063] In formula (1), A independently represents a tetravalent organic group including a cyclic structure. B independently represents an alkylene group having 6 or more carbon atoms which may contain a divalent heteroatom. Q independently represents an arylene group having 6 or more carbon atoms which may contain a divalent heteroatom. W represents B or Q. n represents a number from 0 to 100, and m represents a number from 0 to 100. At least one of n and m is a positive number.
[0064] A in the formula (1) represents a tetravalent organic group including a cyclic structure, and is particularly preferably any of the tetravalent organic groups represented by the following structural formulas.
[0065] [Chemical formula 2]
[0066]
[0067] In addition, the atomic bond of the non-bonded substituent in the above structural formula is bonded to the carbonyl carbon forming the cyclic imide structure in the general formula (1).
[0068] In addition, B in formula (1) is independently an alkylene group having 6 or more carbon atoms which may contain a divalent heteroatom, preferably an alkylene group having 8 or more carbon atoms. More preferably, B in formula (1) is any of the alkylene groups having an aliphatic ring represented by the following structural formulas.
[0069] [Chemical formula 3]
[0070]
[0071] In addition, the atom bond of the non-bonded substituent in the above structural formula is bonded to the nitrogen atom forming the cyclic imide structure in the general formula (1).
[0072] Q is independently an arylene group having 6 or more carbon atoms which may contain a divalent heteroatom, and preferably an arylene group having 8 or more carbon atoms. More preferably, Q in formula (1) is any of the arylene groups having an aromatic ring represented by the following structural formulas.
[0073] [Chemical formula 4]
[0074]
[0075] In the formula (1), n is a number of 0 to 100, preferably a number of 0 to 70. In the formula (1), m is a number of 0 to 100, preferably a number of 0 to 70. At least one of n and m is a positive number.
[0076] As the polymer maleimide, commercially available products such as BMI-2500, BMI-2560, BMI-3000, BMI-5000, BMI-6000, and BMI-6100 (all manufactured by Designer Molecules Inc.) can be used. The cyclic imide compound may be used alone or in combination of two or more.
[0077] (A2) Polymerization initiator
[0078] The component (A2) of the present invention is a reaction initiator for curing the low dielectric heat dissipation film composition. The polymerization initiator (A2) is not particularly limited, and examples thereof include thermal radical polymerization initiators, thermal cationic polymerization initiators, thermal anionic polymerization initiators, and photopolymerization initiators.
[0079] Examples of the thermal radical polymerization initiator include methyl ethyl ketone peroxide, methyl cyclohexanone peroxide, methyl acetoacetate peroxide, acetylacetone peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)propane, 1,1-bis(tert-butylperoxy)cyclododecane, 4,4-di(tert-butylperoxy)butyl valerate, 2,2-bis(tert-butylperoxy)butane, 1,1-bis(tert-butylperoxy)-2-methylcyclohexane, tert-butyl hydroperoxide, and p-menthane hydroperoxide. hydroperoxide), 1,1,3,3-tetramethylbutyl hydroperoxide, tert-hexyl hydroperoxide, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, α,α'-bis(tert-butylperoxy)diisopropylbenzene, tert-butyl peroxide isopropylbenzene, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, isobutyryl peroxide peroxide), 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, cinnamic acid peroxide, m-toluoyl peroxybenzoic acid, benzoyl peroxide, diisopropyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di(3-methyl-3-methoxybutyl peroxydicarbonate), bis(4-tert-butylcyclohexyl) peroxydicarbonate, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, isopropyl peroxyneodecanoate, 1,1,3,3,-tetramethylbutyl peroxyneodecanoate, 1- Cyclohexyl-1-methylethyl ester, tert-hexyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 1-cyclohexyl-1-methylethyl peroxy-2-ethylhexanoate, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-butyl peroxymaleate, tert-butyl peroxylaurate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate, 2,5-dimethyl-2,Organic peroxides such as 5-bis(benzoylperoxy)hexane, tert-butyl peroxyacetate, tert-hexyl peroxybenzoate, tert-butyl peroxy m-toluoylbenzoate, tert-butyl peroxybenzoate, bis(tert-butylperoxy)isophthalate, tert-butyl peroxymonocarbonate, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)diphenyl ketone, etc.;
[0080] 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis[N-(2-methylpropyl)-2-methylpropionamide], 2,2'-azobis[N-(2-methylethyl)-2-methylpropionamide], 2,2'-azobis(N-hexyl-2-methylpropionamide), 2,2'-azobis(N-propyl-2-methylpropionamide), 2,2'-azobis(N-ethyl-2-methylpropionamide), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis[N-(2- Azo compounds such as 1,1'-azobis(methyl 1-cyclohexanecarboxylate) are preferred, and dicumyl peroxide, di-tert-butyl peroxide, isobutyryl peroxide, 2,2'-azobis(N-butyl-2-methylpropionamide) and 2,2'-azobis[N-(2-methylethyl)-2-methylpropionamide] are more preferred, and dicumyl peroxide, di-tert-butyl peroxide and isobutyryl peroxide are more preferred.
[0081] Examples of the thermal cationic polymerization initiator include aromatic iodonium salts such as (4-methylphenyl)[4-(2-methylpropyl)phenyl]iodonium cation, (4-methylphenyl)(4-isopropylphenyl)iodonium cation, (4-methylphenyl)(4-isobutyl)iodonium cation, bis(4-tert-butyl)iodonium cation, bis(4-dodecylphenyl)iodonium cation, (2,4,6-trimethylphenyl)[4-(1-methylethyl acetate)phenyl]iodonium cation; and diphenyl[ An aromatic sulfonium salt such as a 4-(phenylthio)phenyl]sulfonium cation, a triphenylsulfonium cation, and an alkyltriphenylsulfonium cation, preferably a (4-methylphenyl)[4-(2-methylpropyl)phenyl]iodonium cation, a (4-methylphenyl)(4-isopropylphenyl)iodonium cation, a triphenylsulfonium cation, and an alkyltriphenylsulfonium cation, and more preferably a (4-methylphenyl)[4-(2-methylpropyl)phenyl]iodonium cation and a (4-methylphenyl)(4-isopropylphenyl)iodonium cation.
[0082] Examples of the thermal anionic polymerization initiator include imidazoles such as 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole; amines such as triethylamine, triethylenediamine, 2-(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)undec-7-ene, tris(dimethylaminomethyl)phenol, and benzyldimethylamine; and phosphines such as triphenylphosphine, tributylphosphine, and trioctylphosphine. Preferably, 2-methylimidazole, 2-ethyl-4-methylimidazole, triethylamine, triethylenediamine, 1,8-diazabicyclo(5,4,0)undec-7-ene, triphenylphosphine, and tributylphosphine are used; and more preferably, 2-ethyl-4-methylimidazole, 1,8-diazabicyclo(5,4,0)undec-7-ene, and triphenylphosphine are used.
[0083] The photopolymerization initiator is not particularly limited, and examples thereof include benzoyl compounds (or benzophenone compounds) such as benzophenone, and in particular, benzoyl compounds (or benzophenone compounds) having a hydroxyl group on the carbon atom at the α-position of the carbonyl group such as 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, and 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one; and α-alkylaminobenzophenones (alkylaminobenzophenones) such as 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone and 2-(4-methylbenzyl)-2-dimethylamino-1-(4-morpholino-4-yl-phenyl)-butane-1-one. Acylphosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bisacylmonoorganic phosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide; benzoin ether compounds such as benzoin isobutyl ether; acetophenone diethyl ketal and other ketal compounds; thioxanthone compounds; acetophenone compounds, etc. In particular, since the radiation generated by UV-LED is a single wavelength, when UV-LED is used as a light source, it is effective to use a photopolymerization initiator of an α-alkylaminophenone compound or an acylphosphine oxide compound having an absorption spectrum peak in the region of 340 to 400 nm.
[0084] These (A2) components can be used alone or in combination of two or more. The content of the (A2) component is not particularly limited, but is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 8 parts by mass, and even more preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the (A1) component. Within this range, the composition for low dielectric heat dissipation film can be fully cured, and the low dielectric constant of the low dielectric heat dissipation film can be easily maintained.
[0085] Furthermore, the relative dielectric constant of the cured product of the bismaleimide resin composition as component (A) at a frequency of 10 GHz is 3.5 or less, preferably 3.3 or less, and more preferably 2.0 or more and 3.0 or less. If the relative dielectric constant is greater than 3.5, the dielectric constant of the low dielectric heat dissipation film composition becomes high, which is not preferred.
[0086] In addition, the relative dielectric constant in the present invention refers to the value measured by curing the composition to be measured at 180°C for 2 hours, making the cured product into a test piece of 30 mm in length, 40 mm in width and 100 μm in thickness, and then connecting a network analyzer (E5063-2D5 manufactured by Keysight Technologies) and a strip line (manufactured by KEYCOM Corp.).
[0087] [(B) Boron nitride particles]
[0088] The component (B) of the present invention improves the thermal conductivity of the low dielectric heat dissipation film of the present invention.
[0089] The (B) boron nitride particles are not particularly limited, but preferably contain boron nitride particles with a hexagonal crystal structure. It is known that boron nitride particles with a hexagonal crystal structure have a high thermal conductivity in the a-axis direction. By utilizing this property, a film with a high thermal conductivity can be obtained (see Figure 1 ).
[0090] The aspect ratio of the a-axis direction to the c-axis direction of the boron nitride particles with a hexagonal crystal structure is not particularly limited, but is preferably 2 or more, and more preferably 5 to 10,000.
[0091] When the aspect ratio is 2 or more, the (B) boron nitride particles are no longer spherical and have a high thermal conductivity in the a-axis direction. When the aspect ratio is 10,000 or less, high filling is possible. In addition, the major diameter and minor diameter of 100 boron nitride particles are measured by SEM (scanning electron microscopy, for example, 3D Real Surface View Microscope VE-8800 manufactured by KEYENCE CORPORATION can be used), and the average value of each is calculated, and the ratio of the major diameter to the minor diameter is defined as the aspect ratio.
[0092] Furthermore, the ratio Ia / Ic of the intensity Ia in the a-axis direction (100 face) of the boron nitride particles measured by an X-ray diffraction device to the intensity Ic in the c-axis direction (002 face) is preferably 0.25 or more, and more preferably 0.3 to 50. By setting in this way, a film having a high thermal conductivity in the thickness direction of the film can be obtained. In addition, the intensity ratio Ia / Ic is measured, for example, using an X-ray diffraction device SmartLab (manufactured by Rigaku Corporation). The intensity ratio Ia / Ic is a value obtained by scanning 2θ=10° to 90° using CuKα rays at 45kV and 100mA, and calculating the diffraction peak intensity Ia in the a-axis direction (100 face) of the boron nitride particles corresponding to 41.6° and the diffraction peak intensity Ic in the c-axis direction (002 face) of the boron nitride particles corresponding to 26.8°, and calculating the value.
[0093] Furthermore, as a reference for clarifying the orientation state of the boron nitride particles, the difference in thermal conductivity between the surface direction and the thickness direction of the film can also be measured. Preferably, the difference in thermal conductivity between the surface direction and the thickness direction of the film is measured and the difference in thermal conductivity is 0.5 W / m·K or more, and more preferably 1 W / m·K or more. If it is 0.5 W / m·K or more, at least a portion of the boron nitride particles are oriented in the thickness direction of the film, so that anisotropy can be imparted to the thermal conductivity (see Figure 2 ).
[0094] In the present invention, for example, the thermal conductivity can be set to be a value based on Japanese Industrial Standard (JIS) R 1611:2010 by using a laser flash method (device name: LFA 447 Nanoflash, Company).
[0095] Boron nitride particles of different shapes can be further used simultaneously. The shape of the boron nitride particles used simultaneously is not particularly limited, and for example, flaky, granular, spherical, fibrous, elliptical, etc. can be listed, wherein, preferably flaky, granular, spherical, elliptical, further preferably flaky, granular. If it is these shapes, it is easy to highly fill the boron nitride particles in the composition. In addition, the boron nitride particles can be used directly in the state of primary particles, and can also be made into agglomerates for use.
[0096] The average particle size of the boron nitride particles is not particularly limited. For example, the median particle size measured by a laser diffraction particle size distribution measuring device is preferably 0.01 to 500 μm, more preferably 0.05 to 300 μm, and further preferably 0.1 to 100 μm. Within this range, the boron nitride particles can be highly filled. In addition, two or more boron nitride particles of different particle sizes can be used simultaneously.
[0097] The amount of the component (B) to be added is preferably 50 to 2,000 parts by mass, more preferably 100 to 1,500 parts by mass, based on 100 parts by mass of the maleimide resin composition of the component (A).
[0098] In addition, for the purpose of improving the kneading property and affinity with the resin, boron nitride particles treated with a surface treatment agent such as a silane coupling agent can be used. Examples of silane coupling agents include alkyl-modified alkoxysilanes such as methyltrimethoxysilane, methyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, and n-octyltriethoxysilane; aryl-modified alkoxysilanes such as phenyltrimethoxysilane and phenyltriethoxysilane; amino-modified alkoxysilanes such as 3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltrimethoxysilane; 3-[ω-methoxy(polyethylene oxide)]propyltrimethoxysilane, ω-methoxytri(ethylene oxide); 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltriethoxysilane, and other (meth)acryloyl-modified alkoxysilanes; 3-isocyanopropyltriethoxysilane, 3-isocyanopropyltrimethoxysilane, and other alkoxysilanes containing isocyanate; glycidyloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, and other epoxy-modified alkoxysilanes.
[0099] [(C) ingredient]
[0100] The present invention may further contain at least one selected from epoxy resins, phenylene ether resins, styrene resins, and phenol resins as component (C).
[0101] The epoxy resin is not particularly limited, and a commonly known epoxy resin having two or more epoxy groups in one molecule can be used. For example, bisphenol A epoxy resin, bisphenol E epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, naphthalene skeleton modified novolac epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, xylene novolac epoxy resin, bisphenol A novolac epoxy resin, brominated bisphenol A epoxy resin, brominated phenol novolac epoxy resin, trifunctional phenol epoxy resin, tetrafunctional phenol epoxy resin, naphthalene epoxy resin, naphthylene ether (naphthylene ether) ether) type epoxy resin, biphenyl type epoxy resin, phenol aralkyl type epoxy resin, biphenyl aralkyl type epoxy resin, naphthol aralkyl type epoxy resin, alicyclic epoxy resin, dicyclopentadiene type epoxy resin, aralkyl novolac type epoxy resin, polyol type epoxy resin, among which bisphenol A type epoxy resin, bisphenol F type epoxy resin, naphthalene skeleton modified novolac type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, biphenyl type epoxy resin, phenol aralkyl type epoxy resin, biphenyl aralkyl type epoxy resin, alicyclic epoxy resin, dicyclopentadiene type epoxy resin are preferred, and bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenol novolac type epoxy resin, biphenyl type epoxy resin, alicyclic epoxy resin, dicyclopentadiene type epoxy resin are further preferred.
[0102] The phenylene ether resin is not particularly limited, and examples thereof include resins having a structure represented by the following formula (2).
[0103] [Chemical formula 5]
[0104]
[0105] R 1 ~R 8The groups are independently selected from hydrogen atom, saturated hydrocarbon group having 1 to 12 carbon atoms, and aromatic hydrocarbon group having 6 to 12 carbon atoms, preferably hydrogen atom, saturated hydrocarbon group having 1 to 6 carbon atoms, or aromatic hydrocarbon group having 6 to 12 carbon atoms, and more preferably hydrogen atom or saturated hydrocarbon group having 1 to 6 carbon atoms. Examples of the saturated hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, and butyl; cycloalkyl groups such as cyclopentyl and cyclohexyl; and groups obtained by substituting part or all of the hydrogen atoms bonded to the carbon atoms of these groups with halogen atoms such as fluorine, bromine, and chlorine, cyano, glycidyloxy, mercapto, or amino, for example, halogenated monovalent saturated hydrocarbon groups such as trifluoropropyl and chloropropyl; cyanoalkyl groups such as β-cyanoethyl and γ-cyanopropyl; 3-glycidyloxypropyl, 3-mercaptopropyl, and 3-aminopropyl. Among them, methyl, cyclohexyl, and the like are preferred, and methyl is particularly preferred. Examples of aromatic hydrocarbon groups include aryl groups such as phenyl, tolyl, naphthyl, and biphenyl; and aralkyl groups such as benzyl, phenethyl, and phenylpropyl. It may also be a group obtained by replacing part or all of the hydrogen atoms bonded to the carbon atoms of these groups with halogen atoms such as fluorine, bromine, and chlorine or cyano groups. Among them, R is preferably 1 ~R 8 At least one of them is a group selected from a hydrogen atom and a methyl group.
[0106] n' is an integer of 1 to 30, preferably 1 to 20, and more preferably 1 to 10. m' is an integer of 0 to 30, preferably 0 to 20, and more preferably 0 to 10. Within this range, the viscosity is less likely to increase when added to the low dielectric heat dissipation film composition, which is preferred.
[0107] X is a group selected from a single bond and a saturated hydrocarbon group having 1 to 12 carbon atoms, and is preferably a single bond and a saturated hydrocarbon group having 1 to 6 carbon atoms. 1 ~R 8 same.
[0108] The styrene resin is not particularly limited, and examples thereof include resins having a structure represented by the following formula (3).
[0109] [Chemical formula 6]
[0110]
[0111] R 9It is a group selected from a hydrogen atom, a saturated hydrocarbon group having 1 to 12 carbon atoms, an alkenyl group having 1 to 12 carbon atoms, and an aromatic hydrocarbon group having 6 to 12 carbon atoms, preferably a hydrogen atom, a saturated hydrocarbon group having 1 to 6 carbon atoms, an alkenyl group having 1 to 10 carbon atoms, or an aromatic hydrocarbon group having 6 to 12 carbon atoms, and more preferably a hydrogen atom, a saturated hydrocarbon group having 1 to 6 carbon atoms, or an alkenyl group having 1 to 10 carbon atoms. As saturated hydrocarbon groups, alkyl groups such as methyl, ethyl, propyl, and butyl groups can be exemplified; cycloalkyl groups such as cyclopentyl and cyclohexyl groups; and groups obtained by replacing part or all of the hydrogen atoms bonded to the carbon atoms of these groups with halogen atoms such as fluorine, bromine, and chlorine, cyano, glycidyloxy, mercapto, or amino groups, such as trifluoropropyl, chloropropyl, and other halogenated monovalent saturated hydrocarbon groups; cyanoalkyl groups such as β-cyanoethyl and γ-cyanopropyl groups; 3-glycidyloxypropyl, 3-mercaptopropyl, and 3-aminopropyl groups. Among them, methyl, cyclohexyl, and the like are preferred, and methyl is particularly preferred. As alkenyl groups, vinyl, allyl, propenyl, hexenyl, styryl, cyclopentenyl, cyclohexenyl, and dicyclopentenyl groups can be exemplified. Among them, vinyl, styryl, and cyclopentenyl groups are preferred. As examples of aromatic hydrocarbon groups, aryl groups such as phenyl, tolyl, naphthyl, and biphenyl groups can be cited; and aralkyl groups such as benzyl, phenethyl, and phenylpropyl groups can be cited. The group may be a group in which a part or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with a halogen atom such as fluorine, bromine or chlorine, or a cyano group.
[0112] The phenolic resin is not particularly limited, and any commonly known phenolic resin may be used. Examples thereof include phenol novolac resins, naphthalene ring-containing phenolic resins, phenol aralkyl phenolic resins, aralkyl phenolic resins, aralkyl phenolic resins containing biphenyl skeletons, biphenyl phenolic resins, dicyclopentadiene phenolic resins, alicyclic phenolic resins, and heterocyclic phenolic resins.
[0113] When the component (C) is added to the low dielectric heat dissipation film composition of the present invention, the amount of the component (C) is preferably 1 to 50 parts by mass, more preferably 5 to 30 parts by mass, based on 100 parts by mass of the maleimide resin composition of the component (A).
[0114] Furthermore, in addition to the above-mentioned components (A) to (C), the low dielectric heat dissipation film composition of the present invention may contain an inorganic filler, an antioxidant, a flame retardant, etc. as necessary.
[0115] [Inorganic filler]
[0116] Inorganic fillers other than the boron nitride particles of the component (B) are not particularly limited, and examples thereof include silica, calcium carbonate, potassium titanate, glass fiber, silica balloon, glass balloon, alumina, aluminum nitride, beryllium oxide, barium titanate, barium sulfate, zinc oxide, titanium oxide, magnesium oxide, antimony oxide, aluminum hydroxide, magnesium hydroxide, etc., preferably silica, alumina, aluminum nitride, and zinc oxide. By including these inorganic fillers, the thermal expansion coefficient of the cured product of the composition for low dielectric heat dissipation film can be reduced.
[0117] There is no particular restriction on the particle size of the inorganic filler material. For example, the median particle size measured by a laser diffraction particle size distribution measuring device is preferably 0.05 to 50 μm, more preferably 0.1 to 40 μm, and further preferably 0.5 to 30 μm. If it is within this range, it is easy to evenly disperse the inorganic filler material in the composition for low dielectric heat dissipation film, and the inorganic filler material will not precipitate over time, so it is preferred. Furthermore, the particle size is preferably less than 50% of the film thickness. If the particle size is less than 50% of the film thickness, it is easy to evenly disperse the inorganic filler material in the composition for low dielectric heat dissipation film, and it is also easy to evenly apply it to the low dielectric heat dissipation film, so it is preferred.
[0118] The content of the inorganic filler is not particularly limited, but is preferably 1 to 50 parts by mass, more preferably 5 to 40 parts by mass, and further preferably 10 to 30 parts by mass relative to 100 parts by mass of the maleimide resin composition of component (A). Within this range, the thermal expansion coefficient of the composition for low dielectric heat dissipation film can be effectively reduced, and after being formed into a film and fully cured, it will not become brittle, so it is preferred.
[0119] [Antioxidant]
[0120] The antioxidant is not particularly limited, and examples thereof include octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)acetate, neododecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, dodecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, ethyl α-(4-hydroxy-3,5-di-tert-butylphenyl)isobutyrate, octadecyl α-(4-hydroxy-3,5-di-tert-butylphenyl)isobutyrate, and ethyl α-(4-hydroxy-3,5-di-tert-butylphenyl)isobutyrate. Phenolic antioxidants such as octadecyl di-tert-butyl-4-hydroxyphenyl) propionate, 2-(n-octylthio)ethyl 3,5-di-tert-butyl-4-hydroxyphenylacetate, 2-(n-octadecylthio)ethyl 3,5-di-tert-butyl-4-hydroxyphenylacetate, 2-(n-octadecylthio)ethyl 3-(3,5-tert-butyl-4-hydroxyphenyl) propionate, 2-(2-octadecanoyloxyethylthio)ethyl 7-(3-methyl-5-tert-butyl-4-hydroxyphenyl) heptanoate, and 2-hydroxyethyl 7-(3-methyl-5-tert-butyl-4-hydroxyphenyl) propionate;
[0121] Sulfur antioxidants such as 3,3'-didodecyl thiodipropionate, 3,3'-dihexadecyl thiodipropionate, 3,3'-dioctadecyl thiodipropionate, 3,3'-ditridecyl thiodipropionate, and pentaerythritol tetrakis (3-dodecylthiopropionate);
[0122] Phosphorus antioxidants such as tridecyl phosphite, triphenyl phosphite, tris(2,4-di-tert-butylbenzene) phosphite, 2-ethylhexyl diphenyl phosphite, diphenyl tridecyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, pentaerythritol diphosphite distearyl, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate, 2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphocyclopentene-6-yl]oxy]-N,N-bis[2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphocyclopentene-6-yl]oxy]-ethyl]ethylamine
[0123] The content of the antioxidant is not particularly limited, but its content in the low dielectric heat dissipation film composition is preferably 0.00001 to 5% by mass, more preferably 0.0001 to 4% by mass, and further preferably 0.001 to 3% by mass. Within this range, the mechanical properties of the low dielectric heat dissipation film composition are not changed and oxidation of the low dielectric heat dissipation film can be prevented.
[0124] [Flame retardant]
[0125] The flame retardant is not particularly limited, and examples thereof include phosphorus-based flame retardants, metal hydrates, and halogen-based flame retardants.
[0126] Examples include red phosphorus, ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate; inorganic nitrogen-containing phosphorus compounds such as phosphoramide; phosphoric acid, phosphine oxide, triphenyl phosphate, tricresyl phosphate, trixyl phosphate, tolyl diphenyl phosphate, cresyl di-2,6-diphenyl phosphate (cresyl di-2,6-xylenyl phosphate) Phosphazene compounds such as phosphate, resorcinol tetraphenyl diphosphate, 1,3-phenylene bis(di-2,6-ditolyl phosphate), bisphenol A-bis(diphenyl phosphate), 1,3-phenylene bis(diphenyl phosphate), divinyl phenylphosphonate, diallyl phenylphosphonate, di(1-butenyl) phenylphosphonate, phenyl diphenylphosphonate, methyl diphenylphosphonate, bis(2-allylphenoxy)aphosphazene, and ditolyl aphosphazene; melamine phosphate, melamine pyrophosphate, melamine polyphosphate, melam polyphosphate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene Phosphorus flame retardants such as -10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide; metal hydrates such as aluminum hydroxide hydrate and magnesium hydroxide hydrate; halogen flame retardants such as hexabromobenzene, pentabromotoluene, ethylenebis(pentabromobenzene), ethylenebistetrabromophthalimide, 1,2-dibromo-4-(1,2-dibromoethyl)cyclohexane, tetrabromocyclooctane, hexabromocyclododecane, bis(tribromophenoxy)ethane, brominated polyphenylene ether, brominated polystyrene, and 2,4,6-tris(tribromophenoxy)-1,3,5-triazine.
[0127] The content of the flame retardant is not particularly limited, but its content in the low dielectric heat dissipation film composition is preferably 0.01 to 5% by mass, more preferably 0.05 to 4% by mass, and further preferably 0.1 to 3% by mass. Within this range, the low dielectric heat dissipation film can be imparted with flame retardancy without changing the mechanical properties of the low dielectric heat dissipation film composition.
[0128] [Low dielectric heat dissipation film]
[0129] The low dielectric heat dissipation film of the present invention can be easily obtained by molding the following low dielectric heat dissipation film composition into a film. The low dielectric heat dissipation film composition comprises the following components (A) and (B):
[0130] (A) a maleimide resin composition;
[0131] (B) Boron nitride particles,
[0132] The component (A) contains the following components (A1) and (A2):
[0133] (A1) a maleimide resin having at least two maleimide groups in one molecule;
[0134] (A2) a polymerization initiator,
[0135] The maleimide equivalent of the component (A1) is 0.1 mol / 100 g or less, and the relative dielectric constant of the cured product of the component (A) at a frequency of 10 GHz is 3.5 or less.
[0136] The thickness of the low dielectric heat dissipation film is not particularly limited, and can be changed according to the particle size of the boron nitride particles of the (B) component used, for example, 10 μm to 10 mm, preferably 20 μm to 5 mm, and more preferably 30 μm to 2 mm. If the thickness is greater than 10 μm, the strength of the low dielectric heat dissipation film becomes higher; if the thickness is less than 10 mm, the thermal resistance when the low dielectric heat dissipation film is installed becomes smaller.
[0137] In addition, it is preferred that a releasable substrate is attached to at least one side of the low dielectric heat dissipation film of the present invention. The releasable substrate is not particularly limited as long as it is a substrate that can be peeled off after the resin constituting the low dielectric heat dissipation film of the present invention is cured or semi-cured, and examples thereof include fluorine-based substrates, fluorine-based films, and PET films treated with a release agent.
[0138] The thickness of the releasable substrate is not particularly limited and can be selected according to the purpose, but is preferably 10 μm to 1,000 μm.
[0139] The resin film with mold release properties can be optimized according to the type of the insulating resin, and specifically, there can be listed PET (polyethylene terephthalate) film coated with fluorine resin, PET film coated with silicone resin, PTEF (polytetrafluoroethylene), ETFE (poly (ethylene-tetrafluoroethylene)), CTFE (polychlorotrifluoroethylene) and other fluorine resin films, etc. The low dielectric heat dissipation film of the present invention becomes easy to handle and can prevent the adhesion of foreign matter such as dust.
[0140] The low dielectric heat dissipation film of the present invention may be in a cured state or in an uncured state. As a method of using the low dielectric heat dissipation film, when the peelable substrate is provided, after peeling it off, the low dielectric heat dissipation film is clamped between the wiring substrate and the semiconductor, and heated and pressed or fixed with screws, thereby obtaining heat dissipation. As the temperature during heating, it is preferably 100°C to 300°C, more preferably 120°C to 250°C, and further preferably 150°C to 200°C. As the pressure during crimping, it is preferably 0.01MPa to 100MPa, more preferably 0.05MPa to 80MPa, and further preferably 0.1MPa to 50MPa.
[0141] The relative dielectric constant of the cured product of the low dielectric heat dissipation film composition of the present invention at a frequency of 10 GHz is preferably 5.0 or less, more preferably 4.8 or less, and even more preferably 2.0 or less and 4.5 or more. Within this range, it can be suitably used as a heat dissipation film for high frequencies.
[0142] The thermal conductivity of the low dielectric heat dissipation film in the thickness direction is preferably 4 W / m·K or more, and more preferably 6 W / m·K or more. Within this range, the heat generated by the electronic component can be sufficiently dissipated.
[0143] Example
[0144] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0145] Maleimide (A1-1)
[0146] 200 g (1.0 mol) of 1,12-diaminododecane and 207 g (0.95 mol) of pyromellitic anhydride were added to 196 g of N-methylpyrrolidone, and stirred at room temperature for 3 hours, and then stirred at 150°C for 3 hours. 196 g (2.0 mol) of maleic anhydride, 82 g (1.0 mol) of sodium acetate, and 204 g (2.0 mol) of acetic anhydride were added to the obtained solution, and stirred at 80°C for 1 hour. Then, 500 g of toluene was added, and after further washing and dehydration, the solvent was distilled off under reduced pressure to obtain bismaleimide (A1-1) represented by the following formula (molecular weight is 3,500, maleimide equivalent is 0.057 mol / 100 g).
[0147] [Chemical formula 7]
[0148]
[0149] Maleimide (A1-2)
[0150] A maleimide compound represented by the following formula (BMI-3000, manufactured by Designer Molecules Inc., molecular weight: 4000, maleimide equivalent: 0.050 mol / 100 g)
[0151] [Chemical formula 8]
[0152]
[0153] Maleimide (A1-3)
[0154] A maleimide compound represented by the following formula (BMI-2500, manufactured by Designer Molecules Inc., molecular weight: 3500, maleimide equivalent: 0.062 mol / 100 g)
[0155] [Chemical formula 9]
[0156]
[0157] Maleimide (A1-4)
[0158] A maleimide compound represented by the following formula (BMI-1500, manufactured by Designer Molecules Inc., molecular weight: 2100, maleimide equivalent: 0.095 mol / 100 g)
[0159] [Chemical formula 10]
[0160]
[0161] Maleimide (A1-5)
[0162] 252 g (1.0 mol) of KAYAHARD AA (manufactured by Nippon Kayaku Co., Ltd.) and 207 g (0.9 mol) of pyromellitic anhydride were added to 350 g of N-methylpyrrolidone, and the mixture was stirred at room temperature for 3 hours, and then stirred at 120° C. for 3 hours. 196 g (2.0 mol) of maleic anhydride, 82 g (1.0 mol) of sodium acetate, and 204 g (2.0 mol) of acetic anhydride were added to the obtained solution, and the mixture was stirred at 80° C. for 1 hour. Then, 500 g of toluene was added, and the mixture was further washed with water and dehydrated, and the solvent was removed by distillation under reduced pressure to obtain bismaleimide (A1-5) represented by the following formula (molecular weight is 1800, and maleimide equivalent is 0.110 mol / 100 g).
[0163] [Chemical formula 11]
[0164]
[0165] Maleimide (A1-6)
[0166] A maleimide compound represented by the following formula (BMI-2300, manufactured by Daiwa Fine Chemicals Co., Ltd., molecular weight: 400, maleimide equivalent: 0.500 mol / 100 g)
[0167] [Chemical formula 12]
[0168]
[0169] (A2-1) Dicumyl peroxide "PERCUMYL D" (manufactured by NOF CORPORATION)
[0170] (A2-2) tert-Butyl peroxy-2-ethylhexyl carbonate "PERBUTYL E" (manufactured by NOF CORPORATION)
[0171] (A2-3) Triphenylphosphine (manufactured by Kishida Chemical Co., Ltd.)
[0172] (B-1) scaly boron nitride particles "MGP" (manufactured by Denka Company Limited., average particle size 10 μm)
[0173] (B-2) Flake-like boron nitride particles "Flakes 250-3" (manufactured by 3M, average particle size 500 μm)
[0174] (B-3) scaly boron nitride particles "UHP-S2" (manufactured by SHOWA DENKO KK, average particle size 0.5 μm)
[0175] (B-4) Granular boron nitride particles "SGPS" (manufactured by Denka Company Limited., average particle size 12 μm)
[0176] (C-1) Epoxy resin "FOLDI-E201" (manufactured by Nissan Chemical Corporation)
[0177] (C-2) Phenylene ether resin "SA9000" (manufactured by Saudi Basic Industries Corporation)
[0178] (C-3) Epoxy resin "jER-828" (manufactured by Mitsubishi Chemical Corporation)
[0179] [Preparation of cured product]
[0180] The components (A1) and (A2) were mixed at the blending ratio shown in Table 1 while being heated to 60°C, filled into a mold of 30 mm long x 40 mm wide x 100 μm thick, and cured at 180°C for 2 hours.
[0181] In addition, component (A), component (B) or components (A) to (C) were mixed in the blending ratio shown in Table 1 and kneaded at 70°C using a two-roll hot rolling mill. Then, the mixture was crushed and filled into a mold of 10 cm long × 10 cm wide × 10 cm thick, and then hot pressed and cured at 180°C × 2 hours. The obtained cured product was cut into a specified thickness to prepare a low dielectric heat dissipation film.
[0182] [Measurement of relative dielectric constant]
[0183] The prepared cured product was connected to a network analyzer (E5063-2D5 manufactured by Keysight Technologies) and a strip line (manufactured by KEYCOM Corp.) to measure the relative dielectric constant of the cured product of the component (A). The results are shown in Table 1 below.
[0184] Furthermore, the low dielectric heat dissipation film produced was completely cured under the conditions of 180° C.×2 hours to produce a low dielectric heat dissipation film cured product, and the relative dielectric constant was measured in the same manner. The results are shown in Table 1 below.
[0185] [Determination of thermal conductivity]
[0186] The low dielectric heat dissipation film cured products obtained in Examples 1 to 7 and Comparative Examples 1 to 3 were punched out to a diameter of 1 cm, and the entirety thereof was coated with carbon black. The test pieces were used as test pieces and the laser flash method (LFA 447 Nanoflash, The thermal conductivity was measured using a 100% molten-salt syrup (manufactured by TECHNOLOGY CO., LTD.). The results are shown in Table 1 below.
[0187] [Table 1]
[0188]
[0189] The numbers on the right side of (A1-1) to (A1-6) represent the maleimide equivalent (mol / 100 g) of the maleimide resin.
[0190] As shown in Table 1, the low dielectric heat dissipation film of the present invention has a low relative dielectric constant and a high thermal conductivity, and therefore is useful as a heat dissipation film that can cope with high frequencies.
[0191] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any technical solution having substantially the same configuration and having the same function and effect as the technical concept described in the claims of the present invention is included in the technical scope of the present invention.
Claims
1. A composition for low dielectric heat dissipation film, characterized in that: It contains the following components (A) and (B): (A) a maleimide resin composition; (B) Boron nitride particles, The component (A) contains the following components (A1) and (A2): (A1) a maleimide resin represented by any one or more of the following (A1-1) and (A1-3); (A2) a polymerization initiator, The maleimide equivalent of the component (A1) is 0.057 mol / 100 g or more and 0.1 mol / 100 g or less, and the relative dielectric constant of the cured product of the component (A) at a frequency of 10 GHz is 3.5 or less, 2. The composition for low dielectric heat dissipation film according to claim 1, characterized in that: The boron nitride particles of the component (B) include boron nitride particles having a hexagonal crystal structure.
3. The composition for low dielectric heat dissipation film according to claim 1, characterized in that: The ratio Ia / Ic of the intensity Ia in the a-axis direction (100 plane) and the intensity Ic in the c-axis direction (002 plane) of the boron nitride particles of the component (B) measured using an X-ray diffractometer is 0.25 or more.
4. The composition for low dielectric heat dissipation film according to claim 2, characterized in that: The ratio Ia / Ic of the intensity Ia in the a-axis direction (100 plane) and the intensity Ic in the c-axis direction (002 plane) of the boron nitride particles of the component (B) measured using an X-ray diffractometer is 0.25 or more.
5. The composition for low dielectric heat dissipation film according to any one of claims 1 to 4, characterized in that It further contains at least one selected from epoxy resins, phenylene ether resins, styrene resins, and phenol resins as component (C).
6. A low dielectric heat dissipation film, characterized in that: This is a molded product of the composition for low dielectric heat dissipation film according to any one of claims 1 to 4.
7. A low dielectric heat dissipation film, characterized in that: This is a molded product of the composition for low dielectric heat dissipation film according to claim 5.
8. The low dielectric heat dissipation film according to claim 6, characterized in that: The difference in thermal conductivity between the surface direction and the thickness direction of the low dielectric heat dissipation film is 0.5 W / m·K or more.
9. The low dielectric heat dissipation film according to claim 7, characterized in that: The difference in thermal conductivity between the surface direction and the thickness direction of the low dielectric heat dissipation film is 0.5 W / m·K or more.
Citation Information
Patent Citations
Polyphenylene ether resin composition, prepreg, metal-clad laminate, and printed wiring board
JP2010059363A
Polyphenylene ether resin composition, prepreg, metal-clad laminate and printed-wiring board
JP2010275342A
Resin composition, prepreg, laminate, resin sheet, printed wiring board and semiconductor device
JP2012255059A
Heating cooker
JP2016114287A
Boron-nitride powder and resin composition containing same
CN105026312A